Ideologi Media pada Pemberitaan Nusantara Sebagai Ibu Kota Baru Indonesia - Firdaus Marsun; Sadakita Br. Karo; Wiwien Wirasati (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article reports the research results on framing three national media portals, namely Detik.com, Kompas.com, and Tempo.Co regarding the decision to name Nusantara for the new capital city of Indonesia (IKN) in East Kalimantan. This research aims to reveal whether the framing reflects each media’s ideology. The paradigm of this research is constructivism with Robert M.Entman’s framing analysis method. This paper adopts the social construction of reality, ideology, and media as the substantive theory and media framing as The text theory. The results showed that the three media frames for naming Nusantara on IKN still contained problems but differed in focus. Detik.com frames it as a power process, while Kompas.com and Tempo.co as a democratic process. The Kompas.com and Tempo.co frames have reflected their media ideology. Meanwhile, Detik.com is more pragmatic from the media business aspect.